2011
DOI: 10.1007/s12010-011-9276-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sucrose and Trehalose on Stability, Kinetic Properties, and Thermal Aggregation of Firefly Luciferase

Abstract: In this study, we used sugars as stabilizing additives to improve the thermostability and to inhibit aggregation of firefly luciferase. The combination of sucrose and trehalose has a strong stabilizing effect on firefly luciferase activity and prevents its thermoinactivation. These additives can also increase optimum temperature. It has been shown that the presence of both sucrose and trehalose can inhibit thermal aggregation of firefly luciferase and decrease bioluminescence decay rate. In order to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…B, maximum activity of naked luciferase was recorded at 25 °C, but this activity decreased with increasing of temperature above 25 °C. These findings are consistent with previous studies and confirm that optimum temperature for activity of the luciferase is around 22–28 °C.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…B, maximum activity of naked luciferase was recorded at 25 °C, but this activity decreased with increasing of temperature above 25 °C. These findings are consistent with previous studies and confirm that optimum temperature for activity of the luciferase is around 22–28 °C.…”
Section: Resultssupporting
confidence: 93%
“…Luciferase is inactivated at temperatures above 30°C, and thereupon analytical applications of this enzyme are limited [12,13]. So far, different methods have been used to improve the thermal stability of firefly luciferase; for example, site-directed mutagenesis [14][15][16][17][18], and modification of solvents by adding stabilizers such as sucrose, trehalose [19,20], sorbitol, and proline [21].…”
Section: Introductionmentioning
confidence: 99%
“…We noticed that this decay globally followed a hyperbolic curve (i.e. linear when plotted as Log/Log, Figure S2B), as is often observed in luciferase bioluminescence experiments [23,24]. So, this hyperbolic decline is probably due to intrinsic properties of the luminescence physical process.…”
Section: Camp-inhibitory Response To Chk Is Independent Of the Methodsupporting
confidence: 68%
“…Another characteristic of this method using GloSensor is the long-term decay of the stimulatory signals observed especially beyond 30 minutes after FSK. This decline could be caused by a loss of cellular ATP, the cofactor of luciferase, after extended cAMP synthesis or/and by a thermal aggregation of the firefly luciferase [24]. More probably it is due to intrinsic properties of the luminescence physical process, since this decay was surprisingly following a hyperbolic curve (i.e., linear when plotted as Log/Log, Figure S2B) [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…NHDC effect on BAA, AOA, and PPA thermal stability Ligand binding could affect the stability of enzymes, and it has been reported that glycosidic ligands may show some general stabilization effect on proteins. In fact, the thermal stability of many pharmaceutical or industrial proteins is enhanced by the presence of these molecules (Gheibi et al, 2006;Rasouli et al, 2011;James and Mcmanus, 2012;Zaroog et al, 2013). In order to test the potential effect of NHDC on alpha-amylases stability, thermal-induced loss of enzymes activity was monitored over time in the presence and absence of NHDC ( Figure 11).…”
Section: Putative Binding Site Of Nhdc On Baa and Aoa: Docking Experimentioning
confidence: 99%